Getting biofortified food on everyone’s plate: HarvestPlus 2019 annual report - HarvestPlus (International Food Policy Research Institute, 2020)
HarvestPlus is committed to making food systems healthier and more inclusive to benefit the world’s most vulnerable people—particularly smallholder farming families in low- and middle-income countries. The COVID-19 pandemic and efforts to contain it bring into clear focus the urgency of helping these people become more resilient in the face of health and other threats to their well-being. Our 2019 Annual Report, "Getting Biofortified Food on Everyone’s Plate," shows how we engage an expanding range of partners to broaden the reach and impact of micronutrient-rich biofortified crops and foods that contribute to better health outcomes, improved livelihoods, and better lives. Our goal is to make biofortification available to all who can benefit from it.